2017
DOI: 10.1111/jora.12332
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Pathways From Adverse Childhood Experiences to High School Dropout Among High‐Risk Adolescents

Abstract: Adverse childhood experiences (ACEs) are associated with an increased risk for school dropout. This study examined pathways from childhood adversity to school dropout through academic, behavioral, emotional, and social pathways. Data were collected prospectively from 728 adolescents and their caregivers who participated in the Longitudinal Studies of Child Abuse and Neglect and from child protective services records. Path analyses revealed a direct association between ACEs and dropout, as well as indirect effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 67 publications
1
23
1
Order By: Relevance
“…This deviation could be explained by the fact that this study sample consisted of older children. Previous studies suggest that childhood maltreatment was linked to an increased risk in school disengagement and failure [22,23]. In contrast, our analysis indicated that child maltreatment was not a risk factor for dropping out of high school.…”
Section: Discussioncontrasting
confidence: 79%
“…This deviation could be explained by the fact that this study sample consisted of older children. Previous studies suggest that childhood maltreatment was linked to an increased risk in school disengagement and failure [22,23]. In contrast, our analysis indicated that child maltreatment was not a risk factor for dropping out of high school.…”
Section: Discussioncontrasting
confidence: 79%
“…The number of children in the United States who have experienced at least one ACE is increasing (Steiner et al, 2012). These students often exhibit problematic behaviors (Morrow & Villodas, 2014) and teachers often lack the knowledge to effectively attend to their students’ social/emotional aspects (Jennings & Greenberg, 2009). Developing social/emotional skills through CTRT would allow teachers to positively impact students’ personal and academic development and boost their own commitment to the teaching profession.…”
Section: Discussionmentioning
confidence: 99%
“…ACE studies looking into academic performance suggest that ACEs also adversely influence educational attainment, as do other research studies on cumulative risk, which have found a relationship between exposure to a greater number of childhood risk factors and fewer years of education (Horan and Widom 2015). Morrow and Villodas (2018) examined the cumulative effect of ACEs on the likelihood of dropping out of high school and found that an additional ACE increases the odds of dropping out of high school by 9%. They found that ACEs directly and indirectly affect high school dropout rates.…”
Section: Aces and Educational Outcomesmentioning
confidence: 97%
“…Research has found that academic achievement is linked to educational attainment, as educational attainment reflects the ability to excel academically and accumulate knowledge over time (Balfanz et al 2007;Morrow and Villodas 2018). Bethell et al (2014) found that there is lower school engagement among U.S. children with exposure to adverse childhood experiences.…”
Section: Aces and Educational Outcomesmentioning
confidence: 99%
See 1 more Smart Citation